Design and Simulation of a Four-Legged Mobile Robot for Autonomous Navigation on a Spacecraft Hull - Motaz Hassan; Kayla Dremann; Ashton Orosa; Emily Metzger; Nathan Doty; Julia Patek; Siamak Farhad; Ajay Mahajan (Journal of Robotics)
This study presents the design and simulation of a four-legged mobile robot engineered for autonomous navigation on the exterior surface of a spacecraft hull. Unlike existing space robotic systems that rely on fixed infrastructure or operate in structured environments, this quadruped robot is designed to traverse complex, nonplanar hull geometries without external support. The robot integrates global path planning using Dijkstra’s algorithm with real-time orientation correction via an onboard MPU-6050 IMU, enabling it to align with waypoints and minimize positional drift during movement. To evaluate performance, a 2D representation of a spacecraft hull was used, and three test runs were conducted. The robot demonstrated the ability to follow the computed optimal path with a positional deviation of less than 0.5% by the third trial. Positional error was quantified per waypoint and summarized using average and standard deviation metrics, while total traversal distances ranged from 65.50 to 63.00 in., approaching the theoretical minimum of 62.70 in. These results highlight the robot’s iterative improvement in trajectory tracking and its potential for future use in autonomous on-orbit servicing and spacecraft inspection applications.